Increasing environmental outcomes with conservation tenders: The participation challenge. Issue 3 (23rd December 2021) - Rolfe, John; Schilizzi, Steven; Iftekhar, Md Sayed
Abstract: Incentive payments to landholders have become increasingly popular as mechanisms to achieve conservation goals. Within these mechanisms economists commonly recommend competitive tenders over fixed rate payment schemes because (a) specialist knowledge of landholders about their own enterprises and costs can be utilized, (b) auction prices are more likely to reflect the marginal value of the resources being used to produce the environmental outcome, and (c) the scope for rent seeking is reduced by competition between landholders. Yet there is very little uptake of conservation tenders as agrienvironmental schemes, potentially because of the difficulties in generating sufficient levels of landholder participation to make tenders effective. In this paper we summarize the efficiency benefits of using competitive tenders, analyze reasons why participation rates may be so low, and suggest potential mechanisms to address this.